2021
DOI: 10.3389/fpls.2021.703667
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Epigenetic Mechanisms Avoid Constitutive Expression of Immune Receptor Gene Subsets

Abstract: The gene pool encoding PRR and NLR immune receptors determines the ability of a plant to resist microbial infections. Basal expression of these genes is prevented by diverse mechanisms since their hyperactivity can be harmful. To approach the study of epigenetic control of PRR/NLR genes we here analyzed their expression in mutants carrying abnormal repressive 5-methyl cytosine (5-mC) and histone 3 lysine 9 dimethylation (H3K9me2) marks, due to lack of MET1, CMT3, MOM1, SUVH4/5/6, or DDM1. At optimal growth con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…In general, Arabidopsis mutant plants with DNA hypomethylation are more resistant to disease and exhibit an elevated SA-dependent response. For example, met1 , drm1/drm2 and drm1/drm2/cmt3 ( ddc ), nrpd1 (PolIV mutant), nrpe1 (PolV mutant), nrpd1/nrpe1 , nrpd2 (subunit shared by PolIV and PolV), drd1 ( defective in RNA-directed DNA methylation ), rdr2 , and dcl2/3/4 are more resistant to the bacterial pathogen Pst ; cmt3 , drd1 , and nrpe1 are more resistant to the obligate biotrophic oomycete pathogen Hyaloperonospora arabidopsidis ( Hpa ; Lopez et al, 2011 ; Dowen et al, 2012 ; Yu et al, 2013 ; Lopez Sanchez et al, 2016 ; Cambiagno et al, 2021 ; Table 1 and Figure 1A ).…”
Section: Dynamics Of Dna Methylation In Response To Biotic Stressesmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, Arabidopsis mutant plants with DNA hypomethylation are more resistant to disease and exhibit an elevated SA-dependent response. For example, met1 , drm1/drm2 and drm1/drm2/cmt3 ( ddc ), nrpd1 (PolIV mutant), nrpe1 (PolV mutant), nrpd1/nrpe1 , nrpd2 (subunit shared by PolIV and PolV), drd1 ( defective in RNA-directed DNA methylation ), rdr2 , and dcl2/3/4 are more resistant to the bacterial pathogen Pst ; cmt3 , drd1 , and nrpe1 are more resistant to the obligate biotrophic oomycete pathogen Hyaloperonospora arabidopsidis ( Hpa ; Lopez et al, 2011 ; Dowen et al, 2012 ; Yu et al, 2013 ; Lopez Sanchez et al, 2016 ; Cambiagno et al, 2021 ; Table 1 and Figure 1A ).…”
Section: Dynamics Of Dna Methylation In Response To Biotic Stressesmentioning
confidence: 99%
“…In addition to DNA methylation on TEs regulating the transcription of neighboring NLR genes ( Dowen et al, 2012 ), some NLR loci or clusters associated with TEs are also controlled by histone marks, such as H3K9me2 ( Lai and Eulgem, 2018 ). Through Arabidopsis mutant screening, the methylation of DNA and H3K9 was observed to regulate resistance against Pst infection ( Cambiagno et al, 2021 ) and infestation by the pest, green peach aphid Myzus persicae ( Annacondia et al, 2021 ). The study revealed that nrpd1 and kyp mutant plants are more resistant to aphids ( Annacondia et al, 2021 ).…”
Section: Histone Modification and Crosstalk With Dna Methylation Modulate Plant Defense Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, DNA methylation, as one of the epigenetic regulation mechanisms, plays crucial roles in plant immunity ( Huang and Jin, 2022 ); for example, Arabidopsis mutants with DNA hypomethylation are more resistant to Pseudomonas syringae pv. tomato ( Pst ) DC3000 and exhibit an elevated salicylic acid (SA)-dependent response ( Dowen et al, 2012 ; Yu et al, 2013 ; Cambiagno et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%